Linear skin markings in common bottlenose dolphins (Tursiops truncatus) from the Indian River Lagoon, Florida. Issue 3 (16th March 2020) - Titcomb, Elizabeth Murdoch; Stevens, Jessie; Sleeman, Anne; Nelson, Brandy; Yrastorza, Luke; Schaefer, Adam M.; Bossart, Gregory D.; Reif, John S.; Mazzoil, Marilyn
Abstract: A previously undescribed skin abnormality, referred to as "linear skin markings" (LSM), has been identified in free‐ranging common bottlenose dolphins ( Tursiops truncatus ) in the Indian River Lagoon, Florida (IRL). The lesions were identified during photo‐identification surveys conducted from 2002 and 2015. LSM presented as distinct, parallel lines running dorso‐ventrally on the torso and varied in length and width. The goals of this study were to determine (1) prevalence of the condition in IRL dolphins, (2) age and sex distribution of affected animals, (3) spatial and temporal distribution patterns, (4) duration of the condition, and (5) development of hypotheses regarding the etiology of the condition. Among 1, 357 individual dolphins identified during the study period, 96 (7.0%) showed evidence of LSM. Nearly all (98.8%) cases with an established home range occurred in the northern and central regions of the IRL. The majority of cases of known sex were female (85%), of which 100% had given birth to one or more calves. The mean age of animals with LSM when first observed was 7.3 with a range of 1–20 years. The maximum observed duration of LSM was 15 years. Once observed, the condition persisted indefinitely. The etiology of LSM has not been established.